Power-aware mapping based-on genetic algorithm for Network-on-Chip - Dong, Wen-Xiao; Shen, Hai-Bin; Quan, Li; Yang, Yi-Wei (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2010)
As the number of components in NoC(Network-on-Chip) increases, power becomes the focus of the design. In this paper, a low communication power mapping algorithm was proposed, which is based-on genetic algorithm and subject to latency constraint. The algorithm encodes the chromosome as an array of integers, and uses irregular crossover and mutation operations. It takes the advantage of population property of genetic algorithm to find low communication power solution efficiently. The results showed that, the proposed algorithm could effectively reduce the communication power to approximately 50% in average.